Odpowiedzi

2010-01-19T16:28:09+01:00
X+2y=-2 ->x=-2-2y
2x-y=1

2(-2-2y)-y=1
-4-4y-y=1
-3y=5 /:-3
y=-⅗
x=-2-2(-⅗)
x=-2+1⅕
x=3⅕
reszty nie umiem ale chociaż jedno zrobiłam ;D
Najlepsza Odpowiedź!
2010-01-19T16:31:58+01:00
1)
x+2y=-2
2x-y=1|*2

x+2y=-2
-4x-2y=2
-3x=0|:(-3)
x=0

0+2y=-2
2y=-2|:2
y=-1

2)
x+4y=-2|*2
3x-8y=10

2x+8y=-4
3x-8y=10
5x=6|:5
x=1,2

1,2+4y=-2
4y=-3,2|:4
y=-0,8

3)
x-2y=3
-2x+y=0|*2

x-2y=3
-4x+2y=0
-3x=3|:(-3)
x=-1

-1-2y=3
-2y=4|:(-2)
y=-2

4)
2x+y=0|*4
5x-4y=3

8x+4y=0
5x-4y=3
13x=3|:13
x=3/13

2*3/13+y=0
6/13+y=0
y=-6/13